The Effect of Dismenorhoe Gymnastics on Decrease Dismenorhoe on Adolescent Principle in Surbakti Village, Simpang Empat District Karo Regency in 2019 - Vera Caroline Barus (Science Midwifery, 2020)
Dismenorrhoea is defined as a symptom of recurrence, or the medical term is called catmenial pelvic pain, which is a condition of a woman who experiences menstrual pain which has a bad effect, causing disruption of daily activities because of the pain she feels. This study aims to determine the relationship of dysmenorrhoea exercise with the reduction of dysmenorrhea in young women in Surbakti Village, Simpang Empat District, Karo Regency in 2019. As for the independent variable (free) is the effect of dysminorrhea exercise and the dependent variable is the decrease in dysmenorrhea. This type of research uses analytic observational with cross sectional approach method. Where the population is 35 young women and the sample used is a total population of 35 young women. Types of data used are primary data taken directly from respondents using a checklist sheet, and secondary data obtained from the Office of the Village Head of Surbakti. The statistical test used is the Chi-Square test α = 0,000. The results of the Chi-Square statistical test obtained p value = 0.000. This means that the p value is smaller than x2 (0.05) and thus Ho is rejected and Ha is accepted, that is, there is a relationship between dysmenorrhoea and dysmenorrhoea exercise in female adolescents in Surbakti Village, Simpang Empat District, Karo Regency in 2019. It is hoped that adolescents will increase their knowledge about the effect of dysmenorrhoea exercise on reducing dysmenorrhea from various information media, especially from health workers so that they can overcome dysmenorrhoea pain.